A ESTREPTOMICINA NO COMBATE À CRIA PÚTRIDA EUROPÉIA DE Apis mellifera L. - Amaral, Erico; Vencovsky, R. (REVISTA DE AGRICULTURA, 2015)
A ESTREPTOMICINA NO COMBATE À CRIA PÚTRIDA EUROPÉIA DE Apis mellifera L.